Identification and evaluation of glutathione conjugate gamma-l-glutamyl-l-cysteine for improved drug delivery to the brain. Issue 12 (12th August 2020) - Fatima, Saman; Mohammad, Taj; Jairajpuri, Deeba Shamim; Rehman, Md Tabish; Hussain, Afzal; Samim, Mohammed; Ahmad, Farhan Jalees; Alajmi, Mohammed F.; Hassan, Md. Imtaiyaz
Abstract: Glutathione (GU), an endogenous antioxidant tripeptide, is frequently transferred in the human brain through N -methyl-d -aspartate receptor (NMDAR), profusely expressed at the blood–brain barrier (BBB) junction. GU, also modifies the characteristics of tight junction proteins (occludin and claudin) at the site of BBB by depolarizing the enzyme, protein tyrosine phosphatase that manifests its usefulness for passive delivery of nanocarriers to the brain. GU, thus, represents itself as an ideal ligand for the surface decoration of nanocarriers to successfully administer them across the brain via receptor-mediated drug delivery pathway. Hence, we have employed here, in-silico approaches to identify the potential GU-like molecules, as appropriate ligand(s) for surface engineering of nanoconstruct with the purpose of attaining targeted drug delivery to the brain. Structure-based virtual screening methods was used to filter PubChem database for the identification of bioactive compounds with >95% structure similarity with GU. We have further screened the compounds against NMDAR using molecular docking approach. Top hits were selected based on their high binding affinities and selectivity towards NMDAR, and their binding pattern was analysed in detail. Finally, all atom molecular dynamics simulation for 100 ns was carried out on free NMDAR and in-presence of the selected GU-like compound, gamma-l -glutamyl-l -cysteine to evaluate complex stability and structural dynamics. In conclusion, gamma-l -glutamyl-l -cysteine may act as potential binding partner of NMDAR which can further be evaluated in drug delivery system to brain across the BBB. Communicated by Ramaswamy H. Sarma